STRUCTURAL, OPTICAL AND ANTIBACTERIAL STUDIES OF PURE & AMINO ACID ADDED SINGLE CRYSTALS - G.P. Bhavanee1, V. Syamala2, K. Umamaheswar3, K.A. Emmanuel4, J. Sai chandra5 and K.V.L.N Murthy6 (Chelonian Research Foundation, 2023)
Alkali, Alkaline earth and transition metal ions doped L-proline single crystals were grown by solution growth technique. Due to variation in the nature of dopant, there is a modification in the growth habit, nonlinear optical property and mechanical hardness of the doped crystals. Fourier transform infrared (FTIR) spectra reveal strong absorption bands occur due to the presence of L-proline. UV–visible spectra show an improvement in the optical transmittance while doping on L- proline. The unit cell parameters and cell volume are obtained by powder X-ray diffractometer. Effect of dopant on the crystal defect on the grown crystals was characterized by Optical Microscopy. Anti-microbial study of the grown crystals was analyzed using gram positive and gram-negative microorganisms. Key words- Solution growth technique, Dopant, Optical Microscopy, Powder X-ray diffractometer.